On Economy in the Valley of the Trebišnjica River - Samardžić, Gligor M (Collection of Papers of the Faculty of Philosophy in Priština, 2014)
We presented here the facts on economy in the valley of the Trebisnjica River and in its surroundings in the antique period. Numerous archaeological findings prove that the valley of the Trebišnjica River was inhabited in the Roman period. On the locality of Panik (valley of the Trebisnjica River) there was a luxurious urban villa (villa urbana), surrounded by several rustic villas (villae rusticae), which leads to the conclusion that the rustic villas were functionally and spatially related to the urban villa. The villas together formed a property. The epigraphic monuments confirm that in the 1st century, in the valley of the Trebišnjica River, there were properties of the Ital family Vesii, ant that these properties were the centres of the great Ital families. The result of the research provide partial image of the properties in Panik. The inhabitants mainly farmed the land, raised cattle, grew wines and did various sorts of craft. The written sources and the archaeological findings indicate basic economic branches in the time of Romans. There are numerous material findings on economic professions in the valley of the Trebišnjica River and in its surroundings. These testimonies possess great historical value, because they indicate economy in the area of East Herzegovina in the antique period. It can be said that the Roman rule brought significant changes in the social and economic life of the Illyrians. It also influenced the economic development of Dalmatia, evident in improving manufacture, more active economy growth, and in the improvement of trading and crafts. Thanks to the increased agricultural and crafts’ manufacture in Illyria, that is Dalmatia, these areas became important exporters of cattle, wood, etc. till the end of the 4th century.